2019
DOI: 10.3390/fluids4030130
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Interaction of Viscous Fingering and Gravitational Segregation in Porous Media

Abstract: Viscous fingering is fluid dynamics instability induced on the displacement front when a less viscous fluid (LVF) displaces a more viscous fluid (MVF), thereby reducing the displacement efficiency. The displacement of a denser fluid by a less dense fluid produces a gravitational tongue. This gravitational segregation also reduces the displacement efficiency. In this study, the three-dimensional structure of the fingering pattern at the viscous fingering to gravitational segregation boundary was examined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…This phenomenon is expected since the minimal or nonexistence of residual oil behind the waterflood front. This observation agrees with study done by Suekane et al, [19] who concluded that viscous fingering could affect the waterflooding efficiency.…”
Section: Ml/minsupporting
confidence: 93%
See 1 more Smart Citation
“…This phenomenon is expected since the minimal or nonexistence of residual oil behind the waterflood front. This observation agrees with study done by Suekane et al, [19] who concluded that viscous fingering could affect the waterflooding efficiency.…”
Section: Ml/minsupporting
confidence: 93%
“…Viscous fingering can affect sweep efficiency which one of the investigations to predict its effect towards the oil recovery rate. A study done by Suekane et al, [19] showed that viscous fingering can reduce the displacement efficiency. They observed several factors viscous fingering occurred because of viscosity ratio, Péclet number, and gravity number.…”
Section: Capillary Number and Instability Numbermentioning
confidence: 99%
“…In a similar vein, a number of authors have looked at the effect of gravity on the viscous-fingering instability: Rogerson & Meiburg (1993b) studied the onset of the viscous-fingering instability with a gravitationally driven shear parallel to the interface using linear stability analysis; Rogerson & Meiburg (1993a), Tchelepi et al (2004), Tchelepi & Orr (1994), , Camhi, Meiburg & Ruith (2000) and Riaz & Meiburg (2003) investigated the nonlinear evolution of the fingering instability using numerical simulations; and Tchelepi & Orr (1994), Berg et al (2010) and Suekane, Koe & Barbancho (2019) examined the nonlinear evolution of the fingering instability using laboratory experiments. While these studies highlight some of the interesting qualitative behaviour that can be observed, they do not provide a full overview of the different dynamical regimes, nor do they provide quantitative predictions for the evolution of the concentration field.…”
Section: Introductionmentioning
confidence: 99%
“…(2004), Tchelepi & Orr (1994), Ruith & Meiburg (2000), Camhi, Meiburg & Ruith (2000) and Riaz & Meiburg (2003) investigated the nonlinear evolution of the fingering instability using numerical simulations; and Tchelepi & Orr (1994), Berg et al. (2010) and Suekane, Koe & Barbancho (2019) examined the nonlinear evolution of the fingering instability using laboratory experiments. While these studies highlight some of the interesting qualitative behaviour that can be observed, they do not provide a full overview of the different dynamical regimes, nor do they provide quantitative predictions for the evolution of the concentration field.…”
Section: Introductionmentioning
confidence: 99%
“…In [118,119], the same method of X-ray computed tomography was used for investigating the interplay between viscous and gravitational fingering observed in vertical miscible displacement under the gravity force in three-dimensional porous media. In particular, the experiments exhibit that, in conditionally stable configurations (when the viscosity contrast and density contrast have a different effect on the interface, so that one of them stabilizes it while the other destabilizes it), the crossover between the stable and unstable displacements exists, depending on the injection velocity.…”
Section: Problem Ii: Two-sided Convection (Rayleigh-taylor Problem)mentioning
confidence: 99%